Metodik för bakteriologisk provtagning från näshålan på får - Fjällström, Marta (2009)
Respiratory infections are one of the major causes of disease in sheep throughout the world. In the beginning of 2008 the Swedish National Veterinary Institute and the Swedish Animal Health Service together started a project about respiratory infections in Swedish sheep. This study is an initial part of that project and the aim of this study was to investigate different sampling possibilities with focus on nasal swabs.